The Elderly and Life’s Channels: The Threads of Life - Elma Jazz Elma-Macrohon (European Scientific Journal, ESJ, 2018)
This study was undertaken with the aim to validate the assumption in JEM’s Theory on Intergenerational Visits to the Elderly, which states that Intergenerational visits promote socialization, that spirals into family solidarity, quality time shared; that affords the elderly parents more meanings, purposes, significance in their lives, the feeling of successfully aging, and make family relationship tighter everytime it happens. It is also to come up with narrative materials from the experiences of the informant-elderly during intergenerational visits, together with children, grandchildren, friends and relatives, before, during, and after the visitation. The method used is narrative inquiry. Interview schedules were used both in Filipino and English. There were recorded interviews and later transcriptions of them, then a story was woven entitled: “The Elderly and Life’s Channels: The Threads of Life”. There were six parents interviewed equal to six families. The characters in the narrations are representatives from these families. Findings proved that, “intergenerational visits to the elderly”, is a key factor to improve the social relationship between children and parents and between and among parents and children. Other findings were on the smooth and rough (conflicts) events in the family, but the latter mended by the faithful observance of intergenerational visits, which serve as the knot that binds family members together, because the former promotes socialization. It is recommended that Intergenerational visits be included in the yearly activities for the elderly people or the senior citizens, by their respective family members, often or even far in-between.